(untitled) (Al-Academy, 2019)
The graphic field invests the visual space then shows the shape by all means of expression that have a certain meaning. The research is interested in studying the iconic form in the modern graphic design through investing names and flags and the extent of their action in the social life and invest them from one to another looked at from viewpoint of trading and consumption and investing their wide popularity. The study problem is manifested in the following question:1- Does the iconic form help in ad circulation?The importance of the research lies in the following:1- Reading the visual iconic form through deciphering its current symbols. The form combines a concept and a case or a form and meaning. The theoretical framework consists of two sections: the first (the concept of the iconic form) and the research methodology used it for describing and analyzing the research samples, based on the analysis items that are drawn from the theoretical framework and the results of the indicators of the analysis items derived from the theoretical framework. They are as follows:• The working of the iconic form• Rendering • The eloquence of the presentation The results and conclusions reached at by the researcher have also been presented